Jamu As Herbal Medicine: A Study Of Health Communication And Philosophy As Cultural Identity - Kartika, Tina; Suharti, Bangun; Sugiyanta, Sugiyanta (Universitas Islam Negeri Raden Intan Lampung, 2023)
The study aimed to describe jamu as herbal medicine, the study of health communication, and philosophy as a cultural identity. The community's herbal medicine consumption habit and the fertile land conditions allow the community planting of various rhizome species as medicines. Indonesians are familiar with the family medicinal plants (TOGA, Tanaman Obat Keluarga), consisting of fruits, vegetables, and rhizomes, as seasoning ingredients. The data were collected through interviews, observations, documentation, and the informants comprised herbal medicine people in business, herbalists, and consumers. Various media were employed, including direct communication, Whatsapp, Instagram, Facebook, pamphlets, brochures, and leaflets on the walls of shops. The findings of this study concern the herbal medicine-based communication health model as a philosophy of identity in Bandar Lampung City, Indonesia. This model increases the awareness of maintaining health and stamina through herbal medicines, besides conventional medical treatment. These medicines help preserve energy, strengthen body endurance, beauty care, and other therapeutic applications.